1995
DOI: 10.1073/pnas.92.23.10516
|View full text |Cite
|
Sign up to set email alerts
|

Association of a M(r) 90,000 phosphoprotein with protein kinase PKR in cells exhibiting enhanced phosphorylation of translation initiation factor eIF-2 alpha and premature shutoff of protein synthesis after infection with gamma 134.5- mutants of herpes simplex virus 1.

Abstract: The protein encoded by the y,34.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
231
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(236 citation statements)
references
References 25 publications
(18 reference statements)
5
231
0
Order By: Relevance
“…Thus, in the absence of this gene, the HSV-1 mutant cannot replicate in normal cells. 33 However, as the activation of mitogen-activated protein kinase (MAPK) kinase (MEK), a critical downstream RAS effector kinase, suppresses the induction of protein kinase R, g 1 34.5-deficient HSV-1 is allowed to replicate in cancer cells with high MEK activity. 32 Previously, we indicated that g 1 34.5-deficient HSV-1 could replicate in oral SCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the absence of this gene, the HSV-1 mutant cannot replicate in normal cells. 33 However, as the activation of mitogen-activated protein kinase (MAPK) kinase (MEK), a critical downstream RAS effector kinase, suppresses the induction of protein kinase R, g 1 34.5-deficient HSV-1 is allowed to replicate in cancer cells with high MEK activity. 32 Previously, we indicated that g 1 34.5-deficient HSV-1 could replicate in oral SCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The adenovirus E1B region is required for virus replication in cells with a functional p53 pathway, but is dispensable in most tumour cells where the p53 or related pathways are disrupted (eg see reference 18). The HSV ICP34.5 gene counteracts the interferon-induced PKR-mediated block to virus replication, 19,20 which is usually disabled in tumour cells. ONYX-O15 has been tested in a variety of clinical situations with maximal success following repeated administration at high dose in head and neck cancer patients [21][22][23] or intra-hepatic artery infusion into liver cancer patients, 24 both combined with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…3,[6][7][8][9][10][11] This gene encodes two functions: the capacity to replicate in the central nervous system cells maps throughout the gene whereas the capacity to block the phosphorylation of the ␣ subunit of the translation initiation factor eIF-2 and thereby prevent premature shutoff of protein synthesis maps in the 3Ј domain of the gene. [12][13][14][15] While ␥ 1 34.5 − mutants discriminate better between normal and malignant cells in terms of cytotoxicity, additional factors are required for total destruction of tumors in experimental animal models. 12,16 Here we report that in a nude mouse xenograft model the tumoricidal effects of infection with mutant R3616 lacking both copies of the ␥ 1 34.5 gene and ionizing radiation were significantly greater than those of R3616 or of radiation alone.…”
Section: Introductionmentioning
confidence: 99%